Regulatory mechanisms of Sesn2 and its role in multi-organ diseases. (February 2021) - Wang(b), Jie; Wang, Shudong; Xiao, Mengjie; Zhang, Jingjing; Wang(a), Jie; Guo, Yuanfang; Tang, Yufeng; Gu, Junlian
Graphical abstract: Abstract: Sestrin2 (Sesn2) is a powerful anti-oxidant that can prevent acute and chronic diseases. The role of Sesn2 has been thoroughly reviewed in liver, nervous system, and immune system diseases. However, there is a limited number of reviews that have summarized the effects of Sesn2 in heart and vascular diseases, and very less literature-based information is available on involvement of Sesn2 in renal and respiratory pathologies. This review summarizes the latest research on Sesn2 in multi-organ stress responses, with a particular focus on the protective role of Sesn2 in cardiovascular, respiratory, and renal diseases, emphasizing the potential therapeutic benefit of targeting Sesn2 in stress-related diseases.